2011
DOI: 10.1002/cjoc.201180360
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of N‐Sulfonylcyclothioureas in Water

Abstract: A sequential one-pot synthesis of N-sulfonylcyclothioureas from N-monosulfonyl diamines, CS 2 and chloroacetic acid at room temperature in water is described. In the absence of highly toxic thiophosgene and organic solvents, this method is environmentally benign. Simple reaction conditions, easy purification of the products, good yields and thioglycolic acid as the useful byproduct are also important attributes of this methodology. The plausible mechanism including tandem reactions is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…7 illustrates that the ratio of lattice oxygen (˛) was 55% for K 2 La 2 Ti 3 O 10 whereas 42.6% for V-doped K 2 La 2 Ti 3 O 10 . At the same time, the ratio of adsorption oxygen (ˇ) was 45% for K 2 La 2 Ti 3 O 10 and 57.4% for V-doped K 2 La 2 Ti 3 O 10 , showing that Vdoped K 2 La 2 Ti 3 O 10 has lower lattice oxygen (˛) ratio [33,34] and higher oxygen vacancy ratio. The oxygen vacancies of the catalyst powders belong to positive centers and are easily exicited to the conduction band as donor band level which is at the bottom of conduction band of the catalyst powders.…”
Section: Influence Of Vanadium Concentration On the Photocatalytic Acmentioning
confidence: 99%
“…7 illustrates that the ratio of lattice oxygen (˛) was 55% for K 2 La 2 Ti 3 O 10 whereas 42.6% for V-doped K 2 La 2 Ti 3 O 10 . At the same time, the ratio of adsorption oxygen (ˇ) was 45% for K 2 La 2 Ti 3 O 10 and 57.4% for V-doped K 2 La 2 Ti 3 O 10 , showing that Vdoped K 2 La 2 Ti 3 O 10 has lower lattice oxygen (˛) ratio [33,34] and higher oxygen vacancy ratio. The oxygen vacancies of the catalyst powders belong to positive centers and are easily exicited to the conduction band as donor band level which is at the bottom of conduction band of the catalyst powders.…”
Section: Influence Of Vanadium Concentration On the Photocatalytic Acmentioning
confidence: 99%
“…Wang et al [11] investigated the effect of cooling rate on the phase transformation of Sr 3 SiO 5 :Eu 2+ . The results demonstrated that rapid cooling was helpful to reduce the impurity phase of Sr 2 SiO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography-mass spectrometry (GC-MS) 3 has been the most widely used method for the determination of organic acids in tobacco and tobacco products due to its rapidity, simplicity, and high sensitivity. 8 Meanwhile, many other approaches such as, high-perfomance liquid chromatography (HPLC), 7,9 ion chromatography, 10 and capillary isotachophoresis 11 have been used and most of them result in excellent resolution and high detection sensitivity. However, all of these methods require a laborious and time-consuming derivatization procedure for sample preparation, due to the high polarity of organic acids.…”
Section: Introductionmentioning
confidence: 99%